Ammonium interference reduced copper uptake by formaldehyde-crosslinked Sargassum sp. seaweed - Ng,Wenfa (PeerJ PrePrints, 2015)
Sargassum sp., a marine brown macroalgae, is an efficient sorbent for various heavy metals at high concentrations. Nevertheless, the efficiency at which seaweed removes heavy metals from dilute solutions and the effect of ammonium on metal removal is not well understood; an issue of importance given the ubiquity of nitrogenous compounds in the environment arising from various surface run-offs. Herein, the effect of ammonium on copper removal (at trace to low concentration) by formaldehyde crosslinked Sargassum sp. (treated SW) was studied. Due to high copper background, equilibrium sorption experiments was inconclusive concerning treated SW’s ability in removing copper (<1000 ppb), but rapid copper sorption observed in kinetic experiments suggested potential feasibility of the process. Within initial copper concentration of 4 to 20 ppm and pH 2 to 5, experiments revealed that, above a threshold concentration of [NH4+-N] of 50 ppm, ammonium impeded copper uptake on treated SW in a concentration-dependent manner. Specifically, sorption kinetics slowed and uptake capacity decreased with increase in [NH4+-N] from 0 to 2500 ppm. Collectively, beyond demonstrating that treated SW could remove copper from dilute solutions, revelations that ammonium reduced copper sorption highlighted the importance of accounting for the effect in data interpretation and modelling.
Keywords: metal adsorption; trace concentration; chemical pretreatment